Monitoring Climate Change and Air Quality Project Initiative: A Case Study of the Collaboration between ECSTAR and TeroSpace in Thailand - Borwonrat Kanchanarat; Umaporn Akkathai; Cattleya Delmaire; Settapong Malisuwan (Journal of Environmental Protection, 2023)
In Thailand, the alteration of weather patterns has resulted in an increase in instances of irregular rainfall, contributing to the occurrence of droughts. The decline of water levels in dams, due to the combined effects of climate change and prolonged droughts, has had a significant impact on agricultural productivity. Drought has a profound effect on the terrestrial biosphere and the atmospheric water cycle and can also contribute to air pollution. Researchers have found a strong correlation between air pollution and drought severity. In response to this pressing issue, the Excellence Center of Space Technology and Research (ECSTAR) at King Mongkut’s Institute of Technology Ladkrabang has joined forces with TeroSpace company to launch an initiative aimed at promoting sustainable growth in Chiang Rai, a province in Thailand known for its rich biodiversity. ECSTAR and TeroSpace’s partnership on the sustainable growth initiative in Thailand’s Chiang Rai province focuses on expanding their collaboration to include international organizations such as the Centre National d’Etudes Spatiales (CNES), which will provide access to satellite imagery and climate and weather information to improve decision-making in various areas of development. CNES is a French organization in charge of space-related activities in France. The collaboration between France and Thailand for this project, in the context of the France-Thailand Year of Innovation 2023, will be crucial for the successful initiation and execution of this research project. The project aims to explore the relationship between air pollution and climate change through the deployment of air quality monitoring devices in designated locations, connected to a global data-sharing network. The results of this research will be valuable to policymakers as they consider the interplay between air pollution and climate change and make efforts to address these challenges.
Keywords: Air Quality Monitoring and Forecasting; Air Quality and Health Impacts; Atmospheric chemistry and aerosols